2022
DOI: 10.1111/bph.15856
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of human plasma reveals decreased production of trimethylamine N‐oxide retards the progression of chronic kidney disease

Abstract: Background and Purpose: Chronic kidney disease (CKD) is a global public health problem and one of the leading causes of all-cause mortality. However, the pathogenic mechanisms and intervention methods for CKD progression are not fully understood.Experimental Approach: Plasma from patients with uraemia and from healthy controls (n = 30 per group) was analysed with LC-MS/MS-based non-targeted metabolomics to identify potential markers of uraemia. These potential markers were validated in the same cohort and a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For clinical use, one appropriate use case may involve an early detection of chronic kidney disease onset, especially as a microvascular complication from diabetes. 30 Multiple studies have probed metabolic differences related to chronic kidney progression using serum or urine metabolomics, [30][31][32][33][34][35] and we highlight some of the differences with our work. First, our work highlights that differences in serum metabolic profiles are not necessarily reflected in sweat.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical use, one appropriate use case may involve an early detection of chronic kidney disease onset, especially as a microvascular complication from diabetes. 30 Multiple studies have probed metabolic differences related to chronic kidney progression using serum or urine metabolomics, [30][31][32][33][34][35] and we highlight some of the differences with our work. First, our work highlights that differences in serum metabolic profiles are not necessarily reflected in sweat.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the gender-specificity and clinical relevance of this CAR-FMO3-TMAO-platelet axis deserves further investigation. In addition to platelet function and thrombotic risk, an increase in the TMAO plasma concentration has also been shown to increase the risk of impaired glucose tolerance 59 , colorectal cancer 60 , chronic kidney disease 61 and overall mortality 62 . Whether drugs interacting with CAR could also influence these TMAO-dependent endpoints deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma levels of TMAO and its precursors are associated with poor prognosis of CKD [22]. Da-Yong Hu et al reported that inhibiting the TMAO biosynthetic pathway attenuated renal injury in a murine model of CKD [23]. Yan-Ni Wang et al demonstrated that the dysregulation of phosphatidylcholine metabolism is involved in CKD pathology [17].…”
Section: Discussionmentioning
confidence: 99%